Efficacy, safety and tolerability of terbinafine for Tinea capitis in children: Brazilian multicentric study with daily oral tablets for 1, 2 and 4 weeks - Talarico Filho, S.; Cucé, L. C.; Foss, N. T.; Marques, Silvio Alencar [UNESP]; Santamaria, J. R. (My University, 1998)
Background: Tinea capitis is a common skin disease seen predominantly in children. The standard therapies for this disease are griseofulvin and ketoconazole. Nevertheless, these drugs have drawbacks in that they are only fungistatic and require treatment for at least 6 weeks. Previous studies with oral terbinafine for the treatment of Tinea capitis have shown that this agent is effective when given for 4 weeks, comparable to an 8-week regimen with griseofulvin. To date there is no data on the use of oral terbinafine in Brazilian children. Objectives: To assess the efficacy, safety and tolerability of oral terbinafine in short-term treatments (1-, 2- and 4-week treatment) of Tinea capitis in children. Patients and methods: One hundred and thirty-two children aged 1-14 years were enrolled in this study, but only 107 were considered for the final efficacy analysis. Diagnosis included clinical assessment and examination by Wood's light. Confirmation was obtained by direct microscopy and culture for fungus. Terbinafine dosage (125 or 250 mg/day) was adjusted according to patient weight. Efficacy was evaluated both by clinical and mycological assessment. Safety and tolerability variables included data on adverse reaction and clinical laboratory evaluations. Results: Mycological evaluation in the follow-up visit at week 12 showed negative direct microscopy and culture results in 48.6, 60.5 and 69.7% patients in groups 1-, 2- and 4-week, respectively (n.s.). At week 12, 84.8% patients in group 4-week achieved clinical cure with a significant difference compared to groups 1- and 2-week, 54.3 and 60.5%, respectively (P < 0.01). Adverse reactions were present in 4.8, 6.8 and 10.9% of patients in groups 1-, 2- and 4-week, respectively. Terbinafine was not associated with clinically relevant increases in liver function tests. Conclusions: Terbinafine is an effective, well tolerated and safe antifungal agent for the treatment of Tinea capitis m children. The shorter duration of treatment resulted in lower cure rates. However, it is important to note that depending on the severity of the disease, a 1-week-only treatment can also be effective in this indication.
Keywords: Antifungal agents; Child; Tinea capitis; alanine aminotransferase; alkaline phosphatase; aspartate aminotransferase; bilirubin; gamma glutamyltransferase; griseofulvin; ketoconazole; terbinafine; brazil; child; clinical trial; controlled study; drug efficacy; drug safety; drug tolerability; female; fluorescence; follow up; fungus culture; gastrointestinal symptom; human; liver function test; major clinical study; male; microscopy; microsporum canis; multicenter study; priority journal; randomized controlled trial; single blind procedure; tinea capitis; trichophyton; urticaria; Administration, Oral; Adolescent; Alkaline Phosphatase; Anorexia; Antifungal Agents; Bilirubin; Brazil; Child, Preschool; Constipation; Diarrhea; Drug Administration Schedule; Female; Headache; Humans; Infant; Male; Microsporum; Naphthalenes; Nausea; Single-Blind Method; Skin; Tablets; Tinea Capitis; Treatment Outcome; Trichophyton